LEGO Star Wars ideas book - Dolan, Hannah; Dowsett, Elizabeth; Hugo, Simon (DK Publishing, 2018)
This book features 200 imaginative play and building ideas, from LEGO projects that take just a few minutes and a handful of bricks, to builds to keep you occupied for hours. Set up a game of LEGO Star Wars skittles, create a pencil pot shaped like your favorite Sith or Jedi, build a fleet of tiny TIEs, design Darth Vader's family tree, and customize a podracer. Challenge a friend to take on a rathtar, mix up your minifigures, stage your favorite movie battle scene with LEGO StarWars bricks-and much, much more! LEGO® Star Wars(TM) Ideas Book is packed with a family friendly range of activities to inspire every LEGO Star Wars fan. What will you build?